Desuccinylation of TBK1 by SIRT5 regulates inflammatory response of macrophages in sepsis - Xuedi Zhang; Chunxiu Ling; Ziying Xiong; Ting Gong; Shuhua Luo; Xiaolei Liu; Lina Zhang; Chaoxiong Liao; Yue Lu; Xiao Huang; Wending Zhou; Shuangnan Zhou; et al. (Cell Reports)
Summary: Tank-binding kinase 1 (TBK1) is a critical signal transducer in the nuclear factor κB (NF-κB) and interferon regulatory factor (IRF) pathways, essential for innate immunity. However, its negative regulation mechanisms remain unclear. This study demonstrates that TBK1 succinylation, regulated by desuccinylase SIRT5, inhibits lipopolysaccharide (LPS)/Toll-like receptor 4 (TLR4)-mediated NF-κB and IRF signaling activation. We identified three key succinylation sites on TBK1: K38, K154, and K692. In endotoxemia and sepsis models, reduced SIRT5 levels in macrophages increased TBK1 succinylation, inhibiting its binding to IRF3 and TRAF2 and suppressing the inflammatory response. In vivo, adoptive transfer of macrophages expressing the succinylation-resistant TBK1-2KR (K154/692R) mutant reversed the inflammatory cytokine suppression caused by SIRT5 deficiency, exacerbating sepsis-induced lung injury. These findings reveal a novel mechanism by which SIRT5 modulates TBK1 activity and macrophage-mediated inflammation during sepsis.